Interpretive multi-criteria valuation of flexibility initiatives on direct value chain. Issue 9 (29th November 2018) - , Sushil
Abstract : Purpose: Activities on direct value chain directly add value to the products/services delivered to the customers. This value addition can be further enhanced by taking up flexibility initiatives on these direct value chain activities. The purpose of this paper is to identify flexibility initiatives on the direct value chain and carry out their valuation. Design/methodology/approach: Since different value addition criteria (i.e. benefits and costs) may be both tangible and intangible, an interpretive valuation based on multi-criteria framework would be desirable. The paper deploys the efficient interpretive ranking process (IRP) for this purpose. It uses total interpretive structural modeling (TISM) to derive weights of criteria based on their respective driving power. The paper also makes a methodological contribution to assess transitive dominance in IRP based on transitivity check as used in the modified TISM process. Findings: The paper uses a multi-criteria valuation to examine the proposition that the flexibility initiatives will add a higher value as we go downstream in the value chain. The flexibility initiatives linked with marketing such as product upgradation and switching, customized services and dynamic pricing are found to be most value adding in character. Research limitations/implications: The main limitation of this study is that it is generic in nature and need to be replicated in multiple case situations. The methodology proposed can be utilized for specific case analysis for flexibility valuation on the direct value chain. Practical implications: The practitioners may be able to use the proposed method of TISM–IRP with improvements in real-life applications. The proposed multi-criteria valuation is interpretive in nature and can be utilized by practicing managers in group settings even if they do not have complete data. Originality/value: The strategy and operations researchers will find promise in the methodology to investigate and prioritize the initiatives planned to enhance flexibility in different value chain activities. The researchers on multi-criteria decision making will find the methodological enhancement proposed in terms of graphically deriving the transitive dominance to be useful in other applications as well.